Digitalization of Basic Education in Nigeria: Problems and Way Forward - Conrad Ugochukwu Ukozor; Salisu Muhammad (Journal of Artificial Intelligence and Digital Economy, 2024)
This paper examined factors that is militating against digitalization of basic school education in Nigeria. Secondary data were used. The secondary data were gathered from print materials and online publications. The paper identified poor funding, shortage of digital facilities, power problem, poor internet connection, higher cost of digital facilities, poor digital skills and knowledge and shortage of digital experts, poor implementation problem, resistant to change and corruption as major problems that have militated against digitalization of basic education in Nigeria. The government should increase the funding of Basic education in Nigeria and more priorities should be given to the development of digital education. The government should provide adequate digital infrastructure facilities in all the Basic schools to aid accessibility and usability. Innovation Hubs/clusters should be set up in areas where they do not exist to make room for the laps that occurs in some areas in Nigeria, existing hubs should also partner with civil society groups to promote capacity building programs on digital education. The government should address the problem of power generation and distribution across the country. The government should invest more in the information communication technology to improve the connectivity level across the country etc.